Circadian Regulation of the Na+/K+-Atpase Alpha Subunit in the Visual System Is Mediated by the Pacemaker and by Retina Photoreceptors in Drosophila Melanogaster - Damulewicz, Milena; Rosato, Ezio; Pyza, Elzbieta (PloS one, 2013)
We investigated the diurnal oscillation in abundance of the catalytic α subunit of the sodium/potassium pump (ATPα) in the brain of Drosophila melanogaster. This rhythm is bimodal and is particularly robust in the glia cells of the lamina, the first optic neuropil. We observed loss of ATPα cycling in lamina glia in behaviourally arrhythmic per(01) and tim(01) mutants and in flies overexpressing the pro-apoptotic gene hid in the PDF-positive clock neurons. Moreover, the rhythm of ATPα abundance was altered in cry(01) and Pdf(0) mutants, in flies with a weakened clock mechanism in retina photoreceptor cells and in those subject to downregulation of the neuropeptide ITP by RNAi. This complex, rhythmic regulation of the α subunit suggests that the sodium/potassium pump may be a key target of the circadian pacemaker to impose daily control on brain activities, such as rhythmic changes in neuronal plasticity, which are best observed in the visual system.